2019
DOI: 10.1039/c9ra07105a
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and theoretical insights into the corrosion inhibition activity of novel Schiff bases for aluminum alloy in acidic medium

Abstract: Novel Schiff bases characterized through spectroscopic techniques and used as anticorrosive agents for aluminium alloy acidic medium. Electrochemical techniques and DFT studies were used to study inhibition effect and molecular interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 61 publications
0
14
0
Order By: Relevance
“…Extensive research on the microstructural and mechanical properties of aluminum alloy AA2219 has revealed its potential applications in the aerospace and marine industry. [1][2][3][4] Owing to its lightweight, low density and high mechanical strength, it is a widely applied alloy in the marine industry. 1,[5][6][7] Generally, it is prone to mild pitting corrosion induced by aggressive chloride ions in seawater and the harsh marine environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive research on the microstructural and mechanical properties of aluminum alloy AA2219 has revealed its potential applications in the aerospace and marine industry. [1][2][3][4] Owing to its lightweight, low density and high mechanical strength, it is a widely applied alloy in the marine industry. 1,[5][6][7] Generally, it is prone to mild pitting corrosion induced by aggressive chloride ions in seawater and the harsh marine environment.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Owing to its lightweight, low density and high mechanical strength, it is a widely applied alloy in the marine industry. 1,[5][6][7] Generally, it is prone to mild pitting corrosion induced by aggressive chloride ions in seawater and the harsh marine environment. 8 The application of organic coatings is an effective way to protect aluminum alloys from corrosion.…”
Section: Introductionmentioning
confidence: 99%
“…In our last work, we synthesized organic anlogoues of Schiff bases and ferrocenyl Schiff bases and investigated them as efficient corrosion inhibitors for aluminium alloy AA2219-T6. 52,53 Following the same research line here in this piece of work, we aimed at the synthesis of ferrocenyl Schiff bases by varying the alkyl chain length in their structure and their corrosion inhibition efficiency in an acidic medium. The main advantage of the synthesis of these molecules lies in the fact that they were easily prepared and showed very good inhibition efficiency towards alloy substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Still, an inhibitor is regarded as one of the most cost-effective and convenient means of ghting corrosion, particularly in acid solutions [7][8][9][10][11][12]. The corrosion inhibitive behavior of aluminium in an acid medium using different organic compounds with polar functions such as sulphur, phosphorous, oxygen, and nitrogen has been documented [13][14][15][16][17][18][19][20][21][22][23]. Several processes in the industry have used inorganic and organic inhibitors for corrosion defense, but due to their toxicity and high cost, research awareness has moved towards the use of e cient, cost-effective, nontoxic, and benign corrosion inhibitors.…”
Section: Introductionmentioning
confidence: 99%